Bolometric terahertz detection based on suspended carbon nanotube fibers. (30th August 2019) - Liu, Yu; Hu, Qianqian; Yin, Jun; Wang, Pengfei; Wang, Yingxin; Wen, Jianguo; Dong, Zhanmin; Zhu, Jia-Lin; Wei, Jinquan; Ma, Wanyun; Sun, Jia-Lin
Abstract: Fast and sensitive detection of terahertz radiation is notoriously difficult, especially the detection at the ambient condition. Here, we fabricated bolometric terahertz photodetectors based on suspended carbon nanotube (CNT) fibers. Because the CNT fibers exhibit a very small heat dissipation area, the heat transport from the CNT fibers to the air is negligible. It ensures the devices can work well at the ambient condition. Additionally, the CNT fibers demonstrate a high responsivity up to 0.54 A W −1 and a short response time of 200 μ s. This implies a performance that is competitive among the terahertz photodetectors based on CNT.